2017
DOI: 10.1145/3092694
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of Business Process Models—A State-of-the-Art Analysis

Abstract: Business process models play an important role in today’s enterprises, hence, model repositories may contain hundreds of models. These models are, for example, reused during process modeling activities or utilized to check the conformance of processes with legal regulations. With respect to the amount of models, such applications benefit from or even require detailed insights into the correspondences between process models or between process models’ nodes. Therefore, various process similarity and matching mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
15

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 62 publications
1
31
0
15
Order By: Relevance
“…They considered business process models as graphs and defined the structural feature between graphs, namely the graph-edit distance, as the criterion of similarity. Many different similarity concepts have been proposed from other studies, and a few comprehensive studies suggested that similarity measures between business process models can support the search and reuse of similar process models [5][6][7]. Despite a rich set of previous studies contributing to the process similarity research, there is still a lack of proper methods for manufacturing processes since the BPM approach has not been actively discussed in manufacturing industry.…”
Section: Related Workmentioning
confidence: 99%
“…They considered business process models as graphs and defined the structural feature between graphs, namely the graph-edit distance, as the criterion of similarity. Many different similarity concepts have been proposed from other studies, and a few comprehensive studies suggested that similarity measures between business process models can support the search and reuse of similar process models [5][6][7]. Despite a rich set of previous studies contributing to the process similarity research, there is still a lack of proper methods for manufacturing processes since the BPM approach has not been actively discussed in manufacturing industry.…”
Section: Related Workmentioning
confidence: 99%
“…They concluded that no modeling technique is better than another. Schoknecht et al (2017) analyzed the similarity of business process models. They defined business models as the sequences consist of activities, events, and connectors.…”
Section: Business Process Modelingmentioning
confidence: 99%
“…However, there is not a united and multi-disciplinary approach to deal with the complexity of workflows. Most research works prefers to have contributions focusing either on scientific workflows or business workflows (for example, see [6] and [7]). Hence, as a new contribution, this paper addresses a solution that has a workflow context alignment from the relatedness aspect of workflows.…”
Section: Motivationmentioning
confidence: 99%
“…In recent years, many business processes and scientific workflow matching algorithms and similarity measures have been developed [6,7]. For example, Starlinger et al [6] proposed domain agnostic similarity measurement methods.…”
Section: Workflow Similarity Assessmentmentioning
confidence: 99%